2021
DOI: 10.3390/ma14051230
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Acoustic Emission Signals Recorded during Freeze-Thaw Cycling of Concrete

Abstract: This manuscript deals with a complex analysis of acoustic emission signals that were recorded during freeze-thaw cycles in test specimens produced from air-entrained concrete. An assessment of the resistance of concrete to the effects of freezing and thawing was conducted on the basis of a signal analysis. Since the experiment simulated testing of concrete in a structure, a concrete block with the height of 2.4 m and width of 1.8 m was produced to represent a real structure. When the age of the concrete was tw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…The first is the F–T action, which proceeds continuously, and the second one is the fracture test performed after a selected number of F–T cycles. Considering that the F–T cycles act as a continuous loading and unloading process, failure occurs due to the progressive damage of the internal structure of concrete, which is reflected in a decrease in the acoustic signal amplitude or a shifting of the dominant frequency, as reported in [ 40 ]. This irreversible damage is then reflected in the AE parameters recorded during the fracture tests.…”
Section: Resultsmentioning
confidence: 99%
“…The first is the F–T action, which proceeds continuously, and the second one is the fracture test performed after a selected number of F–T cycles. Considering that the F–T cycles act as a continuous loading and unloading process, failure occurs due to the progressive damage of the internal structure of concrete, which is reflected in a decrease in the acoustic signal amplitude or a shifting of the dominant frequency, as reported in [ 40 ]. This irreversible damage is then reflected in the AE parameters recorded during the fracture tests.…”
Section: Resultsmentioning
confidence: 99%
“…The paper by [ 57 ] deals with a complex analysis of acoustic emission signals that were recorded during freeze-thaw cycles in test specimens produced from air-entrained concrete. An assessment of the resistance of concrete to the effects of freezing and thawing was conducted on the basis of signal analysis.…”
Section: Description Of the Articles Presented In The Issuementioning
confidence: 99%
“…The results clearly demonstrate that the acoustic emission method can reveal changes (e.g., minor cracks) in the internal structure of concrete, unlike other commonly used methods. The analysis of the acoustic emission signals using a fast Fourier transform revealed a significant shift of the dominant frequency toward lower values when the concrete was subjected to freeze-thaw cycling [ 57 ].…”
Section: Description Of the Articles Presented In The Issuementioning
confidence: 99%
“…The results confirmed that the method based on the nonlinearity of ultrasonic waves was able to more sensitively detect damage resulting from freeze-thaw cycles compared to methods using the relative dynamic elastic modulus or rebound hardness. Topoláˇr et al [19] applied the AE (acoustic emission) method to freeze-thaw cycle monitoring and measured dynamic modulus of elasticity to compare the results. The relative dynamic modulus of elasticity did not show a significant change according to the freeze-thaw cycle with a maximum decrease rate of 3 %.…”
Section: Introductionmentioning
confidence: 99%